Correlation Of Age And BMI With The Incident Of Nausea And Vomiting In Patients Post Sectio Caesarian Operation With Spinal Anesthesia In Aliyah Hospital 2 - Agussalim Ali; Parawansah; Sulastrianah (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background. Postoperative nausea and vomiting are one of the complications experienced by patients with anesthesia and surgery. There are many factors that influence this occurrence, including age and BMI, where young age and obese BMI tend to experience postoperative nausea and vomiting. This is based on the fact that older age is easier to control nausea and vomiting than young people and obese BMI has more fat tissue to store anesthetic drugs so that the side effects of drugs can last longer. Method. This study used an observational analytic method with a cross sectional approach carried out at Aliyah Hospital 2. The number of samples in this study were 38 people who were taken using total sampling technique. Data collection was obtained from filling in the observation sheet and then the data was analyzed using the Fisher's Exact Test statistical test. The dependent variable in this study was postoperative nausea and vomiting and the independent variables were age and BMI. Results. The results of this study found that age did not have a significant relationship with the incidence of postoperative nausea and vomiting at Aliyah Hospital 2 (p = 0.298) and BMI had a significant relationship with the incidence of postoperative nausea and vomiting at Aliyah Hospital 2 (p = 0.019). Conclusion. From this study it can be concluded that the incidence of postoperative nausea and vomiting after spinal anesthesia is higher in patients with older age and excessive BMI.